Numerical Simulation Study on Gas Migration Patterns in Ultra-Long Fully Mechanized Caving Face and Goaf of High Gas and Extra-Thick Coal Seams - Huaming An; Ruyue Gong; Xingxing Liang; Hongsheng Wang (Fire)
The purpose of this study is to understand the law of gas migration in the goaf and reduce the gas on the working face. Taking the N2105 working face of the coal mining industry as the research object, the mathematical model of gas seepage in the goaf was established based on the percolation theory of porous media, and the model was solved. Using Fluent software to simulate the initial pressure, the working face airflow, and gas concentration distribution, different ventilation modes of gas concentration distribution and migration law with different wind speeds after the initial gas pressure. It is concluded that for the first time, the effect of gas on the working face is insignificant, and the influence of the initial pressure on the working surface is gradually revealed. The influence of airflow speed on the goaf is mainly concentrated in the 20~30 m area near the working face, which is affected by the airflow speed of the working face. The gas concentration in the goaf is low, and the fluctuation is obvious. The types of ventilation directly affect the seepage law of goaf gas. The U + I and U + L type ventilation can reduce the gas concentration in the upper corner and f gas seepages from goaf to the working face.